Pengembangan Media Interaktif Materi Tilawati Al-Qur'an Berbasis Masalah Untuk Mengukur Religiusitas Dan Hasil Belajar Siswa SMP - Ryan Ardiansyah Putra; I Wayan Santyasa; I Made Tegeh (Cetta: Jurnal Ilmu Pendidikan, 2026)
This study was motivated by real-world issues identified in eighth-grade Qur'an instruction at SMP Islamic School Harapan Mulia in Denpasar, namely students' low cognitive mastery of the Tajwid rules in the Tilawati series (particularly Volume 5) and the suboptimal development of the affective domain in the form of daily religious attitudes. This gap is caused by the limited availability of effective digital teaching media, where the learning process still relies on one-way delivery of material without problem-solving scenarios. Consequently, students struggle with self-regulated learning and tend to be passive when encountering errors in reciting verses. This study aims to develop and test the feasibility, practicality, and effectiveness of an online interactive media based on Problem-Based Learning (PBL) for the study of Tilawati Al-Qur’an Volume 5 in improving the cognitive learning achievement and religious attitudes of eighth-grade students at SMP Islamic School Harapan Mulia Denpasar. The novelty of this study lies in the integration of the PBL model into a digital platform to simultaneously enhance students’ cognitive (academic achievement) and affective (religious attitudes) aspects—an approach that remains under-explored in Qur’anic education. The research design employed is a research and development (R&D) study using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects were eighth-grade students at Harapan Mulia Islamic Junior High School in Denpasar. The data collection instruments included an expert validation sheet, a response questionnaire, and test instruments in the form of pre-tests and post-tests, which were analyzed using the N-Gain Score technique. The research results indicate that the developed instructional media was rated as “Highly Appropriate” by both content experts and media experts. The implementation of the media proved effective in significantly improving students’ academic achievement, with an average score increase from 54 to 90.5 (N-Gain Score 0.79; High category), and was also effective in enhancing students’ religious attitudes, with an average score of 77%. Student responses to the use of the media also indicated a very good rating, with a percentage of 91.2% in the individual test and 87.1% in the field test. This study concludes that PBL-based interactive media is feasible and effective as an innovation in modern Qur’an education.